Metode Memahami Hadis-hadis Kontradiktif - Anas, Mohamad; Rosyadi, Imron (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2013)
Activity of hadith external criticism (sanad) and also internal criticism (matn) is the obligation of the observers in order to put its existence together with the Koran as the base of religious argumentation. The process of criticism should be done, knowing that there is no guareantee of hadith which are up to the Muslims society categorized of accepted hadith. In addition to a wide variety of methods to criticize sanad, there are also various offers for hadith editorial criticizing. One of them is the science of mukhtalaf al-hadîth. The existence of this knowledge arises when doing data documentation (takhrîj hadîth) in the shade of the same-similar meaning. It will not be separated from the findings of controversial-looking hadith, and therefore the existence of such controversy should be sought in order to offer solutions with a strong suspect and also sort out the existing data to be placed in the proper position. Thus, this paper focuses on any viable solutions when dealing directly with the hadiths suspected controversial